"Tap Dancing on the Racial Boundary": Racial Representation and Artistic Experimentation in the Films of Bill "Bojangles" Robinson - Durkin, Hannah Kate (2008)
This thesis engages with a major paradox in Bill "Bojangles" Robinson's Hollywood image - namely, its concurrent adherences to and contestations of dehumanising racial iconography - to reveal the ways in which performances of "blackness" work to both establish and challenge cultural boundaries. I will consider Robinson's cinematic image in relation to two competing cultural forces: values of what constitutes "blackness" and individual artistic experimentation. My readings will draw upon Richard Dyer's (1986) notion that "the audience is also part of the making of the image," and Eric Lott's (1993) argument that popular culture is "a place where cultures of the dispossessed are routinely commodified and conteste" to reveal the interplay between Hollywood production values, the subjectivities of the audience and Robinson's own interpretation of his roles.